2000
DOI: 10.1177/0095327x0002600206
|View full text |Cite
|
Sign up to set email alerts
|

The Imprint of the Int fad: Response of Kibbutz-Born Soldiers to Military Service in the West Bank and Gaza

Abstract: Israel Army veterans of kibbutz background who had served in the occupied territories during the Intifada were retrospectively asked how this service affected them. Some common themes were disclosed. Service in the territories deepened understanding of the Israeli-Palestinian conflict but increased fear and hate of Arabs. These feelings did not lead to a national extremism, but rather to a rationalistic position demanding a peaceful, political solution. The majority of respondents became firmer in their origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Village residents supported left wing and right‐wing parties to the same extent (see Election to the 18 Knesset: http://www.knesset.gov.il/elections18/heb/results/ballot_results.aspx?city=2800). Furthermore, earlier studies in Israel indicated the importance of political attitudes and the effect of these attitudes on a large range of topics (Dar & Kimhi, ; Kimhi & Sagy, ; Kimhi & Shamai, ; Sagy, ). It is possible that the more right‐wing political attitudes associates with higher identification and support for the current government and higher level of national resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Village residents supported left wing and right‐wing parties to the same extent (see Election to the 18 Knesset: http://www.knesset.gov.il/elections18/heb/results/ballot_results.aspx?city=2800). Furthermore, earlier studies in Israel indicated the importance of political attitudes and the effect of these attitudes on a large range of topics (Dar & Kimhi, ; Kimhi & Sagy, ; Kimhi & Shamai, ; Sagy, ). It is possible that the more right‐wing political attitudes associates with higher identification and support for the current government and higher level of national resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Soldiers who served in these areas, mainly since the eruption of the first Intifada in 1987, are, on the one hand, exposed to constant threat and danger from attacks by the Palestinians; and, on the other hand, they may participate in or witness immoral Israeli conduct and view Palestinian suffering (Gazit, 1999). Studies conducted in Israel found that such service often leads to anti-Palestinian emotions, mistrust, fear, hate, disgust, dehumanization, and prejudice (Dar, Kimhi, Stadler, & Epstein, 2000; Gazit, 1999): H5: Serving in the Israeli army in the West Bank and the Gaza Strip will increase both personal and collective fear and weaken hope.…”
Section: This Studymentioning
confidence: 99%
“…16 The goals of the deployed units are often unclear because of the unfamiliarity with the constabulary role, 17 because of the ambiguity and danger of the situation, 18 or because a political body or the public is undecided about what should be done. 19 A number of studies have stated that the means for operations are inadequate because the rules of engagement are too strict to be successful, 20 or because the soldiers are not able to cope with the complexities of peace support operations. 21 Finally, mutual trust is not optimal or guaranteed when soldiers have not been adequately trained or when they do not have the right attitudes.…”
Section: Mission Commandmentioning
confidence: 99%